Case Report: Development of a thyrotropinoma in a patient with thyroid hemiagenesis - Emil Bartosz Rozenek; Mark Gurnell; Jacek Kunicki; Maria Maksymowicz; Marta Korbonits; Wojciech Zgliczyński; Maria Stelmachowska-Banaś (Frontiers in Endocrinology, 2026)
Thyroid hemiagenesis (THA) is a relatively rare disorder in which one thyroid lobe fails to develop. Although most individuals remain clinically euthyroid, they typically exhibit higher thyrotropin (TSH) concentrations than those with a bilobed thyroid gland, possibly reflecting reduced thyroidal reserve and a chronic compensatory response by pituitary thyrotrophs. While pituitary hyperplasia has been reported in the setting of hypothyroidism in THA, a TSH-secreting pituitary neuroendocrine tumor (thyrotropinoma) has not previously been described in this condition. A 30-year-old woman underwent thyroid function testing during the first trimester of her first pregnancy, which revealed a TSH concentration of 2.57 mIU/L. In accordance with local clinical practice, thyroid ultrasonography was performed and demonstrated absence of the left thyroid lobe, consistent with THA. Given the TSH level >2.5 mIU/L and the potentially limited thyroidal functional reserve associated with THA, subclinical hypothyroidism was diagnosed. To prevent the development of overt hypothyroidism during pregnancy and its associated maternal and fetal complications, levothyroxine therapy was initiated. Over the following years, levothyroxine was progressively uptitrated, but despite development of clinical features of thyrotoxicosis, with raised free thyroid hormone levels, serum TSH remained unsuppressed, prompting evaluation for this discordant thyroid function pattern. Pituitary MRI demonstrated an 11mm macroadenoma. Further investigations revealed an elevated alpha-glycoprotein subunit (α-GSU) level and an attenuated TSH response to TRH stimulation. A trial of a depot somatostatin receptor ligand resulted in a marked reduction in thyroid hormone levels. Together, these findings supported the diagnosis of a thyrotropinoma. Transsphenoidal surgery was performed, and histology confirmed a PIT1 lineage plurihormonal tumor with predominant TSH expression. Following surgery, the patient developed central hypothyroidism and was recommenced on levothyroxine therapy. We report the first documented case of a pituitary adenoma in a patient with THA; notably, the lesion was the rarest pituitary tumor subtype, a thyrotropinoma. This observation raises the possibility of a biological link driven by chronic thyrotroph stimulation, potentially contributing to adenoma formation. A similar feedback-driven mechanism has been proposed to explain cases of coexistence of resistance to thyroid hormone β (RTHβ) and thyrotropinoma. Therefore, in patients with THA receiving levothyroxine therapy, the development of hyperthyroxinaemia with a non-suppressed TSH should prompt consideration of a thyrotropinoma.